PENGARUH UMUR DAN LAMA PENYIMPANAN TERHADAP PERTUMBUHAN BENIH LADA - Saefudin, Saefudin (Pusat Penelitian dan Pengembangan Perkebunan, 2012)
Penelitian untuk mengetahui pengaruh umur dan lama penyimpanan terhadap pertumbuhan benih lada telah dilakukan di Rumah Kaca Kebun Percobaan Sukamulya, Sukabumi, Jawa Barat mulai bulan Januari sampai dengan Desember 2011. Percobaan disusun berdasarkan rancangan acak kelompok faktorial dengan tiga ulangan. Faktor Pertama adalah tiga taraf (umur benih), yaitu 1, 2, dan 3 bulan, sedangkan faktor kedua adalah 5 taraf (lama simpan benih), yaitu 0, 3, 5, 7 dan 9 hari. Jumlah sampel benih untuk pengamatan kondisi kesegaran sebanyak 50 bibit, sedangkan untuk pertumbuhan benih sebanyak 25 benih setiap perlakuan. Parameter yang diamati meliputi kondisi kesegaran benih setelah mendapat perlakuan penyimpanan dan pertumbuhan benih umur 3 bulan. Parameter pertumbuhan terdiri atas tinggi benih, jumlah buku, panjang daun, lebar daun, dan panjang ruas. Data hasil pengamatan selanjutnya dianalisis menggunakan analisis sidik ragam (anova) dilanjutkan dengan uji BNJ taraf 5%. Hasil penelitian menunjukkan bahwa interaksi antara umur benih dan lama penyimpanan berpengaruh terhadap kondisi kesegarannya, sedangkan umur benih dan lama penyimpanan berpengaruh terhadap pertumbuhan benih lada. Apabila benih lada dikeluarkan dari polibagnya, maka benih lada umur 2 bulan yang paling mampu bertahan terhadap penyimpanan dengan lama penyimpanan maksimal 5 hari. THE EFFECTS OF AGE AND STORAGE PERIODS ON THE GROWTH OF ROOTED CUTTINGS OF BLACK PEPPER ABSTRACT To provide good black pepper cuttings grown in polythene bags, it might be costly due to transportation cost should be covered into cost production. The use of rooted cuttings of black pepper is therefore considered as an alternative solution in providing of plant materials being ready to be planted in the fields. A research was carried out at a glass house of Sukamulya Research Station (Sukabumi) from January to Desember 2011. The objective of the study was to investigate the effects of age and storage periods of rooted cuttings on their freshness and growth performances under nursery condition. A randomized factorial design with three replications was used. The age of black pepper cuttings consisted of 1, 2, and 3 months old, while the storage periods were 0, 3, 5, 7 and 9 days. The number of pepper cuttings observed for their freshness levels were 50 cuttings per treatments, whereas those of their growth were 25 cuttings. For evaluation of their freshness, they were calculated based on the percentage of treated cuttings having water content of higher than 75%, while for their growth parameters observed were height of rooted cuttings, number of nudes, leaf length, leaf width, and length of internodes. The data were then analyzed with analysis of variance (anova) followed by HSD test level 5%. The results showed that there were noted interaction between the age and storage periods of rooted cuttings to the freshness and growth of young rooted cuttings. If farmers use rooted cuttings taken out from their polythene bags, then 2-month cutting olds with maximum storage periods of 5 days would give the best treated rooted cuttings having high in performance growth.